Airborne Wind Lidar Measurements of Vertical and Horizontal Winds for the Investigation of Orographically Induced Gravity Waves - Witschas, Benjamin; Rahm, Stephan; Dörnbrack, Andreas; Wagner, Johannes; Rapp, Markus (Journal of Atmospheric and Oceanic Technology, 2017)
Airborne coherent Doppler wind lidar measurements, acquired during the Gravity Wave Life-Cycle (GW-LCYCLE) I field campaign performed from 2 to 14 December 2013 in Kiruna, Sweden, are used to investigate internal gravity waves (GWs) induced by flow across the Scandinavian Mountains. Vertical wind speed is derived from lidar measurements with a mean bias of less than 0.05 m s−1 and a standard deviation of 0.2 m s−1 by correcting horizontal wind projections onto the line-of-sight direction by means of ECMWF wind data. The horizontal wind speed and direction are retrieved from lidar measurements by applying a velocity–azimuth display scan and a spectral accumulation technique, leading to a horizontal resolution of about 9 km along the flight track and a vertical resolution of 100 m, respectively. Both vertical and horizontal wind measurements are valuable for characterizing GW properties as demonstrated by means of a flight performed on 13 December 2013 acquired during weather conditions favorable for orographic GW excitation.